Kegiatan Budaya Sebagai Suatu Alat Interaksi Dan Komunikasi Dalam Pendidikan - Dewi Kartika (Institut Agama Islam Negeri (IAIN) Curup, 2018)
This paper talks about culture which has a role as a communication tool in education. The aim to be achieved in this study is that culture is an element that has influence in the process of education, and has a role as a tool to interact in education. Culture and education are two things that are interconnected. Because in education there is a cultural transmission. To understand the value of cultural activities as an educational tool, we must clarify understanding of basic concepts such as: Creativity is a process in which an individual, as a result of his personal abilities and opportunities and in his interactions with his environment, will look for new and / or original products that are adequate for the situation in question this product can be concrete or abstract. Interaction and communication, Interaction is reciprocal attention between two people (or more) to one another or to an object or third person. Partners in this interaction focus their attention on the same goal (one another or third person or a certain object). This mutual attention is often responded to by gestures, speeches or actions. Whereas Communication means first of all sharing. We share and exchange interests, feelings, thoughts, opinions or information with a series of media codes, which are formed as signals and symbols, which can be understood and used by all communication partners.